Diaphragmatic Peritonectomy versus Full Thickness Diaphragmatic Resection and Pleurectomy during Cytoreduction in Patients with Ovarian Cancer. (18th December 2013) - Pathiraja, P. N. J.; Garruto-Campanile, R.; Tozzi, R.
Abstract : Objectives . Compare the surgical morbidity of diaphragmatic peritonectomy versus full thickness diaphragmatic resection with pleurectomy at radical debulking. Design . Prospective cohort study at the Oxford University Hospital. Methods . All debulking with diaphragmatic peritonectomy and/or full thickness resection with pleurectomy in the period from April 2009 to March 2012 were part of the study. Analysis is focused on the intra- and postoperative morbidity. Results . 42 patients were eligible for the study, 21 underwent diaphragmatic peritonectomy (DP, group 1) and 21 diaphragmatic full thickness resection (DR, group 2). Forty patients out of 42 (93%) had complete tumour resection with no residual disease. Histology confirmed the presence of cancer in diaphragmatic peritoneum of 19 patients out of 21 in group 1 and all 21 patients of group 2. Overall complications rate was 19% in group 1 versus 33% in group 2. Pleural effusion rate was 9.5% versus 14.5% and pneumothorax rate was 14.5% only in group 2. Two patients in each group required postoperative chest drains (9.5%). Conclusions . Diaphragmatic surgery is an effective methods to treat carcinomatosis of the diaphragm. Patients in the pleurectomy group experienced pneumothorax and a higher rate of pleural effusion, but none had long-term morbidity or additional surgical interventions.